Arthritis and Diagnostics in Lyme Disease - Javier A. Quintero (Tropical Medicine and Infectious Disease, 2021)
The diagnosis of Lyme disease, caused by Borrelia burgdorferi, is clinical but frequently supported by laboratory tests. Lyme arthritis is now less frequently seen than at the time of its discovery. However, it still occurs, and it is important to recognize this, the differential diagnoses, and how laboratory tests can be useful and their limitations. The most frequently used diagnostic tests are antibody based. However, antibody testing still suffers from many drawbacks and is only an indirect measure of exposure. In contrast, evolving direct diagnostic methods can indicate active infection.